Aesthetics of Buddhism on Tai Dam woven fabric pattern - Disbanjong, Kontarnrat (Mahachula Academic Journal, 2021)
Aesthetics of Buddhism on Tai Dam woven pattern is an expression of the concept of beauty that values ​​​of goodness and the truth as it appears on the woven fabric pattern, which is a distinctive characteristic of the Tai Dam culture. Which is based on beauty based on the ethical values ​​of 2 levels which are 1. Abstract beauty Emphasize the beauty of Buddhism, including principles of life. Considered a high level of beauty, such as the law of nature the truth of life and the way to end suffering called Noble Truths Principle 4, Law of Karma, Law of Trinity, Trinity of Practice 4, Sangahavatthu 4, Brahmavihara 4, Aprihanigadhamma 7, Saraniyadhamma 6, Sacrifice principles 5. Directions 6, Mangala 38, Principles of Reclusion, Principle of Reclining, Pilakkhama, Honest, Patience, Tolerance, Unity, Humility, Generosity, Sacrifice, Kindness, Mercy Discipline, Comprehension, Self-reliance, which is reflected through the pattern on the woven fabric, namely, species of flora, animal patterns, patterns of things. And patterns, utensils 2. Beauty in concrete levels is a shape beauty and the beauty of the environment that the creator had invented on woven fabric, including the fabric patterns of flora, animal patterns, patterns of things and patterns, utensils. There are decorated with looking glass fabric that has the characteristics of various patterns. That has the meaning consistent with the way of life of the Tai Dam which is related to Buddhism. The decoration of the mirror and the coloration reflecting the emotional feeling and communicate in accordance with the Buddhist principles, namely, indigo, dark or black, yellow, orange, green, red or crimson, white.